2021
DOI: 10.3390/cancers13040632
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profile for Diagnostic and Prognostic Biomarkers in Thyroid Cancer

Abstract: The challenge in managing thyroid nodules is to accurately diagnose the minority of those with malignancy. We aimed to identify diagnostic and prognostic miRNA markers for thyroid nodules. In a discovery cohort, we identified 20 candidate miRNAs to differentiate between noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP) and papillary thyroid carcinomas (PTC) by using the high-throughput small RNA sequencing method. We then selected three miRNAs (miR-136, miR-21, and miR-127) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The miRNAs that have been shown to be consistently upregulated in PTC tissues, when compared with non-neoplastic thyroid, include miR-21, miR-127, miR-136, miR-146b, miR-221, miR-222, and miR-181b [ 79 , 80 , 81 , 82 , 83 ]. MicroRNAs miR-221 and miR-222 negatively regulate p27 protein, a cyclin-dependent kinase inhibitor and a cell-cycle regulator [ 84 ].…”
Section: Molecular Landscape Of Follicular Cell-derived Thyroid Cancermentioning
confidence: 99%
“…The miRNAs that have been shown to be consistently upregulated in PTC tissues, when compared with non-neoplastic thyroid, include miR-21, miR-127, miR-136, miR-146b, miR-221, miR-222, and miR-181b [ 79 , 80 , 81 , 82 , 83 ]. MicroRNAs miR-221 and miR-222 negatively regulate p27 protein, a cyclin-dependent kinase inhibitor and a cell-cycle regulator [ 84 ].…”
Section: Molecular Landscape Of Follicular Cell-derived Thyroid Cancermentioning
confidence: 99%
“…Therefore, novel molecular markers are essential for risk stratification and personalized management of PTC [23]. Previous studies have revealed multiple potential PTC markers, such as miRNAs (miR-136, miR-21, and miR-127) [19], lncRNA SLC26A4-AS1 [24], and Lactate Dehydrogenase A [25]. Fortunately, in this study, we identified a novel potential molecular marker for PTC treatment, i.e., MAP17.…”
Section: Discussionmentioning
confidence: 76%
“…Briefly, constructs (MAP17overexpressing (MAP17) and negative control (NC)) were inserted into an adenovirus-packaging plasmid. After that, the above adenovirus were packaged in HEK293A cells [19]. CAL62 and TPC-1 cells were seeded into 24-well plates, achieving to a cell density of about 2 × 10 5 , and then 5 × 10 10 PFU/mL adenovirus (2 µL) was added into the 24-well plate, and the fresh complete culture medium was replaced after 4-8 h. WB analysis was performed 48 h later.…”
Section: Map17 Overexpression and Knockdownmentioning
confidence: 99%
“…Further, "RNA sequence analysis" was performed to identify new and known "miRNAs" to differentiate between different type of tumors. As a result of which it was found that it was not always the case some types of "miRNAs" were found to be overly expressed in cancer patients including miR-136, miR-21 and miR-127 that could serve as a biomarker for identification of thyroid cancer patients (Park et al, 2021).…”
Section: Mirna Markersmentioning
confidence: 99%